Navigating Crisis Management Strategies: Lessons from Successful Organizations - Yessica Amelia; Ruslaini Ruslaini; Cahyatih Kumandang (LPPM STIE Kasih Bangsa, 2024)
This qualitative research aims to investigate crisis management strategies employed by successful organizations. The study adopts a qualitative approach, utilizing in-depth interviews and documentary analysis as the primary research methods. A purposive sampling technique is utilized to select participants, focusing on leaders and key personnel with extensive experience in crisis management. Data analysis involves thematic analysis, identifying patterns and themes within the collected data. The findings reveal a range of effective crisis management strategies employed by these organizations, including proactive planning, effective communication, and agile decision-making. These insights contribute to a deeper understanding of crisis management practices, providing valuable lessons for organizations facing similar challenges.